Leafhoppers Exitianus atratus and Amplicephalus funzaensis transmit phytoplasmas of groups 16SrI and 16SrVII in Colombia. (6th January 2016) - Perilla‐Henao, L.; Wilson, M. R.; Franco‐Lara, L.
Abstract : The phytoplasmas of groups 16SrI (' Candidatus Phytoplasma asteris') and 16SrVII (' Ca . Phytoplasma fraxini') have been associated with phytoplasma diseases in several urban tree species in Bogotá, Colombia and surrounding areas. The insect vectors responsible for this phytoplasma transmission are unknown. The objectives of this study were to test for the presence of phytoplasmas in leafhopper species (Cicadellidae) collected in areas with diseased trees and to determine the phytoplasma transmission ability of two of these species. Leafhoppers of nine species were collected at two sampling sites and tested by nested or double nested PCR using primers for the 16S rRNA gene. The amplicons were subjected to RFLP and/or sequencing analysis. Phytoplasmas of group 16SrI were detected in morphospecies MF05 ( Haldorus sp.), group 16SrVII in MF07 ( Xestocephalus desertorum ), MF08 ( Empoasca sp.) and MF09 (Typhlocybinae), and both groups 16SrI and 16SrVII in MF01 ( Empoasca sp.), MF02 (Typhlocybinae), MF03 ( Scaphytopius sp.), MF04 ( Amplicephalus funzaensis ) and MF06 ( Exitianus atratus ). Transmission tests to uninfected bean plants ( Phaseolus vulgaris ) were performed using field collected A. funzaensis and E. atratus individuals in separate assays. After 5 weeks, the test plants exposed to individuals of both species of leafhoppers showed symptoms, suggesting phytoplasma infection. Phytoplasma groups 16SrI and 16SrVII were detected in the two groups of exposed plants, indicating that A. funzaensis and E. atratus were able to transmit both groups of phytoplasmas. This is the first report of insect vectors for phytoplasmas of group 16SrVII in the world and of 16SrI in South America.